PENGARUH PIJAT KAKI MENGGUNAKAN MINYAK MELATI TERHADAP NYERI IBU POST OPERASI SECTIO CAESAREA DI RSUD NGUDI WALUYO WLINGI - Zahratu Ikfiyana Habsillah, Hanny; Marsaid, Marsaid; Nataliswati, Tri; Hidayah, Nurul (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Pain is one of the main complaints experienced by mothers after undergoing a sectio caesarean. If not properly managed, pain can lead to delayed recovery and increased risk of complications. Therefore, non-pharmacological pain management is necessary, such as foot massage therapy using jasmine oil extracted from jasmine flowers (Jasminum sambac and Jasminum officinale) through steam distillation, which is considered a safe and effective alternative. Methods: This technique has not been widely applied. This study aimed to determine the effect of foot massage therapy using jasmine oil on pain levels in post-sectio caesarea mothers at RSUD Ngudi Waluyo Wlingi. The research design used was a quasi -experiment with a pretest-posttest control group design. The sample consisted of 60 respondents divided into two groups, selected using purposive sampling according to inclusion criteria. Data collection was carried out using a pain scale observation sheet. Data were analyzed using the Wilcoxon test, Results: The results showed that in the intervention group during the first session, the average pain level decreased from a pretest score of 5.80 to a posttest score of 4.70. In the second session, the pain level decreased from 4.00 to 2.70. The average pain score in post-sectio caesarea mothers decreased from 5.80 to 4.70 (first session) and from 4.00 to 2.70 (second session), with a p-value of 0.000 < 0.05. Conclusion: The Wilcoxon test results indicated a significant effect on pain levels before and after the foot massage using jasmine oil. Therefore, nurses can consider this therapy as a non-pharmacological method to reduce pain in post-sectio caesarea mothers.